2004
DOI: 10.1111/j.0004-8461.2004.01321.x
|View full text |Cite
|
Sign up to set email alerts
|

All delays before radiotherapy risk progression of Merkel cell carcinoma

Abstract: Prolonged waiting times for radiotherapy have resulted in many centres assigning priorities to various patient or diagnostic groups. A high risk of progression on a waiting list is one factor that would reasonably influence the priority. The present descriptive study of 27 patients with Merkel cell carcinoma (MCC) found that a median wait of 24 days for radiotherapy is associated with a high risk of progression. Eleven (41%) of 27 patients developed progressive disease, including five (45%) of 11 patients wait… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0
2

Year Published

2005
2005
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(26 citation statements)
references
References 19 publications
1
23
0
2
Order By: Relevance
“…Radiotherapy techniques were not clearly defined and doses ranged between 45 and 50 Gy to primary sites, 45 and 60 Gy to nodal basins and the start of radiotherapy was only within 4 months of surgery. This is relevant as recurrences typically occur early, therefore delaying adjuvant or even primary radiation may be significant [36].…”
Section: Postoperative Radiotherapymentioning
confidence: 99%
“…Radiotherapy techniques were not clearly defined and doses ranged between 45 and 50 Gy to primary sites, 45 and 60 Gy to nodal basins and the start of radiotherapy was only within 4 months of surgery. This is relevant as recurrences typically occur early, therefore delaying adjuvant or even primary radiation may be significant [36].…”
Section: Postoperative Radiotherapymentioning
confidence: 99%
“…MCC has a tendency to invade dermal lymphatics early in disease progression [93]. A study of 27 patients found that a median wait of 24 days for radiotherapy is associated with a high risk of progression [94,95].…”
Section: Prognosismentioning
confidence: 99%
“…For example, one of our patients died untreated, after waiting for 4 months for appropriate investigations and therapy. Another study found that a median wait of [24 days for RT is associated with a high risk of progression [26].…”
Section: Discussionmentioning
confidence: 99%